Social Media and the Political Campaign Industry in Indonesia - Muninggar Sri Saraswati (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2018)
The use of social media has been expanding rapidly that it recently overwhelmed not only players in Indonesian electoral and political scenes but also general public. While previous studies appeared to put an emphasis on the technological forces (that is, the social media), the political forces (the political parties, politicians or candidates) or cultural forces (the voters or social media users) alone to understand the development, this article argues that the use of social media in electoral campaigning requires mediation by economic forces as represented by the political campaign industry. Based on a series of in-depth interviews with key politicians, campaigners, social media users and media people, the involvement of the political campaign industry in the commodification of social media is found.Â  Such a commodification has resulted in the emergence of buzzing, social media users mobilization and social media monitoring.Â Â